On the Colonial Element in Joseph Wright's English Dialect Dictionary. (25th October 2018) - Ruano-García, Javier
Abstract: This paper takes a preliminary approach to the colonial element of Joseph Wright's English Dialect Dictionary (1896-1905). Drawing on the electronic version of the dictionary that has recently been launched, it examines the entries which refer to the colonial usage of words documented in British dialects, considering the links that Wright made with Australia, Canada, Newfoundland, and New Zealand, as well as the isolated evidence recorded on items used in South Africa and the West Indies. The aim is twofold. Firstly, lexicographical, as this paper explores the role of the colonial material by ascertaining the proportion of words that are cited from the colonies, and analysing the treatment they are given: attention is paid to their lexicographical function, labels, and the evidence provided to support their inclusion. Secondly, I argue that, despite the narrow coverage of Australian, Canadian, Newfoundland and New Zealand Englishes, the data may add to our understanding of the lexical links between British varieties of English and colonial speech of the late 1800s.